Stem Properties of Planted Calamus Scipionum and Daemonorops Angustifolia of Different Ages - Kadir, Roszaini (1997)
Knowledge on anatomical, physical, mechanical and machining properties is necessary in assessing the potential use of rattan but little research has been conducted on the commercially important large diameter species. A total of fifty two stems of two species namely Calamus scipionum Lour. 'Rotan semambu' and Daemonorops angustifolia (Griff.) Mart. 'Rotan getah' from plantation plots were chosen for the study to evaluate the effect of age and height on the properties of rattan. All the anatomical characteristics studied were significantly correlated to age, portion, part (except fibre length, lumen diameter and cell wall thickness) and segment.